2004
DOI: 10.1093/jnci/djh076
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies Using the Aromatase Inhibitor Letrozole and Tamoxifen in a Breast Cancer Model

Abstract: First-line letrozole therapy extends time for tumor progression in this model relative to the other treatment regimens tested. However, further studies are needed to determine the most effective second-line therapy for tumors that progress on letrozole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(138 citation statements)
references
References 25 publications
10
124
3
Order By: Relevance
“…The possibility that blockade of estrogen action and estrogen synthesis may be synergistic was explored by treating mice with the aromatase inhibitor letrozole and the antiestrogen tamoxifen alone and in combination. However, the results in the model indicated that letrozole alone was better than tamoxifen or combined treatments [93]. This result was analogous to results later reported for the ATAC trial [94].…”
Section: Adjuvant Therapy With Tamoxifensupporting
confidence: 87%
“…The possibility that blockade of estrogen action and estrogen synthesis may be synergistic was explored by treating mice with the aromatase inhibitor letrozole and the antiestrogen tamoxifen alone and in combination. However, the results in the model indicated that letrozole alone was better than tamoxifen or combined treatments [93]. This result was analogous to results later reported for the ATAC trial [94].…”
Section: Adjuvant Therapy With Tamoxifensupporting
confidence: 87%
“…MCF-7Ca tumors of mice treated with letrozole initially regressed but gradually resumed growth and had doubled in volume by week 21 of treatment (Brodie et al 2005). Interestingly, it was found that letrozole-resistant tumors did not respond to either tamoxifen or fulvestrant as second-line therapy (Long et al 2004a). These findings are in apparent contrast with the abovementioned reports from LTED in vitro experiments that suggested activity of fulvestrant in cells that had undergone adaptive supersensitivity, a condition that in vitro resembles resistance to AIs .…”
Section: Adaptation To Estrogen Withdrawalmentioning
confidence: 77%
“…The phenomenon of acquired resistance to AIs has also recently been addressed by using MCF-7 cells stably transfected with human aromatase gene (MCF7Ca) (Long et al 2004a, Brodie et al 2005. MCF-7Ca tumors of mice treated with letrozole initially regressed but gradually resumed growth and had doubled in volume by week 21 of treatment (Brodie et al 2005).…”
Section: Adaptation To Estrogen Withdrawalmentioning
confidence: 99%
“…Mice were than injected s.c. daily with the indicated agents: 100 mg per mouse per day (5 Â weekly) plus 10 mg per mouse per day (5 Â weekly) of letrozole or 200 mg per mouse per day (5 Â weekly) of anastrozole and 20 mg kg À1 day À1 (5 Â weekly) of VN/14-1. The doses of letrozole, anastrozole, androstendione and VN/14-1 used are as determined previously (Long et al, 2002(Long et al, , 2004Patel et al, 2004). The mice were treated for the indicated times, after which they were killed by decapitation and blood collected.…”
Section: In Vivo Antitumour Studiesmentioning
confidence: 99%